Análisis Retrospectivo del Distemper Canino - Morbillivirus en los siete cantones de la provincia Bolívar en el periodo 2017 – 2020. - Isa Yallico, Raúl Marcelo (2021)
He prevalence of canine Distemper in the Bolívar province, added to the vertiginous growth of the canine population in the different cantons of the province, leads to requiring an assessment of the risk factors associated with the prevalence of the disease. The objective of this research was to carry out a retrospective study of the prevalence of Canine Distemper - Morbillivirus in the seven cantons of the Bolívar province in the period 2017-2020. Information was obtained from 1041 medical records of canine patients treated during the period 2017-2020, of which 480 met the criteria for a positive case for canine Distemper. In general, the results were the prevalence of Distemper in all the cantons of the Bolívar province, being the canton with the highest number of cases of Distemper diagnosed by number of dogs treated Las Naves (70%), followed by the Canton Caluma (54%) and San Miguel (53%) and to a lesser extent the Guaranda canton (34%). As a conclusion, it was determined that the risk factors for the disease were: vaccination is a protective factor of Distemper, in terms of sex, a greater risk factor is observed in; the females, in climatic levels of the sierra. Finally, it was identified that, in terms of relative risk, there is a greater probability of suffering from Distemper in those puppies from 7 to 11 months of age, not vaccinated of the French Poodle breed and mongrel.